Preliminary investigation on dimer-pyrrole adsorption on aluminum, copper, and silicon surfaces (100): A first principle calculation - Villagracia, Al Rey C. (Animo Repository, 2009)
We calculated ground-state binding energies of dimer-pyrrole (di-Py) on Aluminum (Al), Copper (Cu), and Silicon (Si) surfaces. Adsorption of dimer-pyrrole on these surfaces could provide a way on how to calculate the activation energy for each configuration. These activation energies are vital information in characterizing the electronic properties of conductive polymer-metal interfaces. Recent study has shown that conductive polymer-metal interfaces are good sources of information in designing novel materials for photovoltaic cells1, photocapacitors2, and fuel cells3 applications.